Optimizing Destination Digital Branding Through Motion Graphics Animation: A Collaborative Initiative with Diskominfo Pangandaran - Ganjar Mohamad Disastra; Laksmi Saraswati Hadiansyah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Digital transformation has become a critical success factor in destination marketing within the Tourism 4.0 era. As a leading tourist destination in West Java, Pangandaran Regency faces challenges in adapting to the information consumption trends of modern tourists who prioritize creative and concise visual content. The Department of Communication, Informatics, Statistics, and Journalism (Diskominfo) of Pangandaran Regency holds a strategic role in disseminating tourism information. However, current promotional strategies are still dominated by conventional video content, which is susceptible to audience fatigue and field production constraints. This community engagement initiative aims to diversify promotional media through the creation of motion graphics-based animation videos. This solution was selected due to its superiority in simplifying complex information into entertaining visual narratives (edutainment) and its flexibility in visualizing tourist attractions without being hindered by weather or logistical factors. The implementation method was carried out collaboratively, encompassing pre-production (research and scriptwriting), production (visual asset design and animation), and post-production (editing and final rendering). The primary output of this activity is the availability of high-quality promotional animation assets optimized for multi-platform local government social media networks. This intervention successfully bridges the technical resource gap of the partner while reinforcing the digital branding identity and visual positioning of Pangandaran’s tourism to drive higher tourist engagement.